Effect of tax negotiation on offer, perceived fairness and aggressiveness / Voon Yuen Hoong - Voon, Yuen Hoong (2018)
This experimental study contributes to existing research on a tax authority-tax practitioner negotiation model during tax audits, by providing the first evidence that concession timing matters. Negotiations on tax audits facilitate the interaction between tax practitioners and tax authorities. The role of negotiation in tax audit is to align the different motivations of tax practitioners and tax authorities. This study permits a better understanding of the consequences of concession timing negotiation strategies adopted by the tax authorities on tax practitioners and their final proposed offer. This study extends the negotiation model in other disciplines to include a new variable, tax practitioners’ level of aggressiveness and examines the role of fairness in tax audit negotiations. If tax practitioners perceive that the negotiation strategies adopted by the tax authorities are unfair to them, they may aggressively try to mitigate their tax payable by obtaining aggressive tax planning advice from tax practitioners. Thus, this study offers evidence of the influence of the negotiation strategies adopted by the tax authorities on the tax practitioners’ final proposed offer, their perception of fairness (i.e., distributive justice and procedural justice) and their aggressive stance in the tax audit negotiations. From a practical perspective, this study provides insights to tax authorities in identifying the most appropriate negotiation strategy to collect underreported taxes and establish proper procedures to handle grey area or ambiguous tax issues found during the tax audit period. At the same time, this study also contributes to the extension of the reciprocity and anchoring effects in taxation and the effect of concession timing strategies adopted in taxation negotiations, especially in tax audit negotiations between tax audit officers and tax practitioners.